Intruders or protectors – the multifaceted role of B cells in CNS disorders - Aspden, James W.; Murphy, Matthew A.; Kashlan, Rommi D.; Xiong, Yueyue; Poznansky, Mark C.; Sîrbulescu, Ruxandra F. (Frontiers in Cellular Neuroscience, 2024)
B lymphocytes are immune cells studied predominantly in the context of peripheral humoral immune responses against pathogens. Evidence has been accumulating in recent years on the diversity of immunomodulatory functions that B cells undertake, with particular relevance for pathologies of the central nervous system (CNS). This review summarizes current knowledge on B cell populations, localization, infiltration mechanisms, and function in the CNS and associated tissues. Acute and chronic neurodegenerative pathologies are examined in order to explore the complex, and sometimes conflicting, effects that B cells can have in each context, with implications for disease progression and treatment outcomes. Additional factors such as aging modulate the proportions and function of B cell subpopulations over time and are also discussed in the context of neuroinflammatory response and disease susceptibility. A better understanding of the multifactorial role of B cell populations in the CNS may ultimately lead to innovative therapeutic strategies for a variety of neurological conditions.